Lingua Franca of Cardiogenic Shock: Speaking the Same Language - Long, Ashleigh; Baran, David A. (Frontiers in Cardiovascular Medicine, 2021)
Cardiogenic shock has remained a vexing clinical problem over the last 20 years despite progressive development of increasingly capable percutaneous mechanical circulatory support devices. It is increasingly clear that the published trials of various percutaneous mechanical circulatory support devices have compared heterogenous populations of cardiogenic shock patients, and therefore have not yielded a single result where one approach improved survival. To classify patients, various risk scores such as the CARDSHOCK and IABP-Shock-II scores have been developed and validated but they have not been broadly applied. The Society for Cardiac Angiography and Intervention Expert Consensus on Classification of Cardiogenic Shock has been widely studied since its publication in 2019, and is reviewed at length. In particular, there have been numerous validation studies done and these are reviewed. Finally, the directions for future research are reviewed.